A case study of customer perceptions in determining the product quality of Perodua cars / Ahmad Fikri Abdul Rashid - Abdul Rashid, Ahmad Fikri (Faculty of Business and Management, 2013)
The objective of this research is to study customer perception towards the quality of Perodua cars among customers around Petaling Jaya, Selangor. The respondent selected were 300 Perodua users in Petaling Jaya area. This study is conducted because; based on the data received from Perodua, the number of customer complaint is increasing year by year and at the mean time, the number of sales is also increasing. So, researcher tend to investigate, why customer still choose Perodua, even though lots of issues has arise. Therefore, four independent variables and one dependent variable will be used to examine what is customer perception. All four independent variables are chosen based from the eight dimension of quality as proposed by Garvin (1987). Quality determinant will be the dependent variable for this study. Based on the finding, it shows that all independent variables have a significant relationship. Moreover, as chose by respondents. For the most crucial determinant will be the serviceability. As for conclusion, Perodua seems to provide a good serviceability to their customers; however, they cannot put interest to customers when it comes to the performance, features and reliability of Perodua cars. To add, Perodua must not overlook about this because, based on the result, only two elements have moderate relationship meanwhile for reliability and performance just have a weak relationship.